Serum Creatine Kinase Muscle-Brain Fraction (CK-MB) and Lactate Dehydrogenase (LDH) as Markers of Perinatal Asphyxia in Term Neonates - Kanodia, Piush; Shrestha, Sudesh; Gautam, Santosh; Chawla, Sachin (Journal of Nepalgunj Medical College, 2020)
Background: The enzymes CK-MB & LDH are used as potential predictors of timing and grade of HIE in newborns with perinatal asphyxia.Objectives: To differentiate HIE neonates from non-HIE ones on the basis of significant rise of LDH & CK-MB.Methodology: Prospective cross-sectional analytical study. Among 164 newborns, 82 comprising the cases and 82 neonates comprising the controls met the inclusion and exclusion criteria. The umbilical cord blood samples for CK-MB and LDH was drawn and sent for analysis. A serum CK-MB value >92.6 U/L and LDH value >580 U/L was taken as the cut-off level. Descriptive statistical analyses were done to find the significance between two groups. ROC Curve analysis was performed to find the diagnostic performance of CK-MB and LDH.Results: Out of total 164 neonates studied, 18.3% had moderate HIE & 11%had severe HIE while 56.1%had No HIE. Seventy-two newborns were found to have LDH levels >580 U/L out of which 71 were in case group and 1 was in control group. Among the 164 neonates studied, 7.9% from case group were found to have CK-MB levels >92.6 U/L. Both the results of LDH & CK-MB levels were very significant with P value